Penggunaan Pembelajaran Berbasis Masalah Untuk Meningkatkan Kemampuan Komunikasi Matematis Dan Pengaruhnya Terhadap Self Regulated Learningsiswa Sekolah Menengah Pertama - Mulyani, Has (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2015)
The importance of mathematical and communication skills Self Regulated Learning for students has been widelyrecognized in mathematics education. But still lack a way that can be used in improving keduanya, into theimplementation of the basic idea of this research. Through the application of problem-based learning is expectedto enrich the strategy to improve the communication skills of mathematical and Self Regulated Learningstudents. This research includes studies quasi experimental design with a control group not equivalent. Thisresearch was conducted in SMP Pasundan 2 Bandung, the subject of the entire population of students of classVII SMP Pasundan 2 Bandung and took two samples of class VII. Instruments used include test questions andquestionnaires mathematical communication skills Self Regulated Learning. Quantitative data analysis usingANOVA test two way, followed by Scheffe test. Based on the results of this study concluded that: increase ofmathematical and communication skills Self Regulated Learning Ability Early learners with Mathematics(LAM) high, medium and low learning using Problem Based Learning is better than the increase in mathematicaland communication skills Self-Regulated Learning learners who use the usual learning model. Then this studysuggests that there is a correlation between communication skills matematis and Self Regulated Learning. Thecorrelation coefficient between the two is 0.643 with the criteria of being